The trade effects of a new agreement on services domestic regulation - Roger Yu So; Eddy Bekkers (World Trade Organization (WTO), 2024)
In this paper, we project the impact of the implementation of a Joint Statement Initiative (JSI) on Services Domestic Regulation (SDR). We proceed in three steps. First, we include the WTO SDR Index, a binary score of SDR implementation in 23 sectors and 86 economies, in a gravity equation, estimated with the balance of payments services trade. We take into account domestic services trade to identify the impact of the importer-specific SDR Index by interacting the SDR Index with a border dummy, following an established methodology in the gravity literature. The estimation generates a significant impact of the SDR Index in a series of regressions pooled across all sectors, accounting for other determinants of services trade. Second, we map the estimates together with projected changes in the SDR Index into ad valorem equivalent trade cost changes under the implementation of the negotiated outcome on SDR. Estimated trade cost reductions are 10%, 14%, and 8.5% in lower-middleincome, upper-middle-income, and high-income countries respectively. In dollars, the estimated trade cost reduction of 127 Bn is similar to earlier OECD estimates of the trade cost reduction of the SDR of about 150 Bn. Third, the WTO Global Trade Model, a recursive dynamic computable general equilibrium (CGE) model, is employed to project the economic effects of the SDR outcome which are modelled as resourcesaving reductions in iceberg trade costs. Simulations indicate that global income would increase by 0.3% in the long run (over 10 years), while global exports are projected to rise by 0.8%. The projected gains are largest in lower- and upper-middle-income countries while impacts on non-participants are projected to be marginally positive.
Keywords: F13; F17; 330; Computable General Equilibrium models; gravity estimation; services trade